ICOS and OX40 tandem co-stimulation enhances CAR T-cell cytotoxicity and promotes T-cell persistence phenotype - Moreno-Cortes, Eider; Franco-Fuquen, Pedro; Garcia-Robledo, Juan E.; Forero, Jose; Booth, Natalie; Castro, Januario E. (Frontiers in Oncology, 2023)
Chimeric Antigen Receptor (CAR) T-cell therapies have emerged as an effective and potentially curative immunotherapy for patients with relapsed or refractory malignancies. Treatment with CD19 CAR T-cells has shown unprecedented results in hematological malignancies, including heavily refractory leukemia, lymphoma, and myeloma cases. Despite these encouraging results, CAR T-cell therapy faces limitations, including the lack of long-term responses in nearly 50-70% of the treated patients and low efficacy in solid tumors. Among other reasons, these restrictions are related to the lack of targetable tumor-associated antigens, limitations on the CAR design and interactions with the tumor microenvironment (TME), as well as short-term CAR T-cell persistence.Because of these reasons, we developed and tested a chimeric antigen receptor (CAR) construct with an anti-ROR1 single-chain variable-fragment cassette connected to CD3 by second and thirdgeneration intracellular signaling domains including 4-1BB, CD28/4-1BB, ICOS/4-1BB or ICOS/OX40. We observed that after several successive tumor-cell in vitro challenges, ROR1.ICOS.OX40 continued to proliferate, produce pro-inflammatory cytokines, and induce cytotoxicity against ROR1 + cell lines in vitro with enhanced potency. Additionally, in vivo ROR1.ICOS.OX40 T-cells showed anti-lymphoma activity, a long-lasting central memory phenotype, improved overall survival, and evidence of long-term CAR T-cell persistence.We conclude that anti-ROR1 CAR T-cells that are activated by ICOS.OX40 tandem costimulation show in vitro and in vivo enhanced targeted cytotoxicity associated with a phenotype that promotes T-cell persistence.